Fake Medical News. Doctoring Data: How to Sort Out Medical Advice from Medical Nonsense by Malcolm Kendrick - Bauer, Henry (Journal of Scientific Exploration, 2018)
Fake medical news can kill. Unfortunately, much of the medical news disseminated everywhere is indeed fake in the sense of not trustworthy, perhaps most dangerously in what is generally accepted as sound medical practice. Much of the peer-reviewed mainstream medical literature is not to be trusted, as pointed out by John Ioannidis among many others [1]. This book explains how to improve health and extend lifespan by exercising informed skepticism. The author, Malcolm Kendrick, MD (University of Aberdeen, 1981) who practices in Cheshire (England); he had earlier published The Great Cholesterol Con (John Blake Publishing, 2008), and he posts regularly at https://drmalcolmkendrick.org. When someone is obviously ill, or damaged physically through accident or warfare or other physical violence, modern-day medical practice can be splendidly effective. On the other hand, modern-day medical practice can be dangerously harmful for symptom-free people whose numbers on any of a variety of tests happen to deviate appreciably from a population average. So-called preventive medicine, almost exclusively based on prescription drugs, has a very high risk-to-benefit ratio, not least because the purported benefits have rarely — if ever — been demonstrated in actual practice.